Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Iklan, Kualitas Produk Dan Citra Merek Terhadap Loyalitas Pelanggan - Ashur Harmadi; Guyub Nuryanto; Maritza Nurhaliza Angginami (ARBITRASE: Journal of Economics and Accounting, 2024)
The surge in demand for cosmetics increasingly shows that cosmetics are now considered an important need, comparable to basic needs such as clothing and food. The Wardah cosmetics company has gained recognition as a global brand that not only prioritizes the domestic market in Indonesia, but also pays attention to the skin needs of various countries. The aim of this research is to determine the effect of advertising, product quality and brand image on loyalty through customer satisfaction as an intervening variable at Wardah Cosmetics in Bekasi. The analytical method in this research uses quantitative primary data. The test stages used are validity test, reliability test, classical assumption test, statistical test, coefficient of determination test and path analysis. This research used a questionnaire instrument for 100 respondents. The sampling technique uses Purposive Sampling. Analysis tool with Multiple Pregression. The results of this research show that advertising, product quality and brand image have effect on loyalty. Meanwhile, advertising, product quality and brand image do not have effect on loyalty through customer satisfaction with Wardah cosmetics in Bekasi.